Scholastic affect gender, maternity and the history of emotions - Monagle, Clare 1973- (Cambridge University Press, 2020)
Scholastic theologians made the Virgin Mary increasingly perfect over the Middle Ages in Europe. Mary became stainless, offering an impossible but ideologically useful vision of womanhood. This work offers an implicit theory of the utility and feelings of women in a Christian salvationary economy. The Virgin was put to use as a shaming technology, one that silenced and effaced women's affective lives. The shame still stands to this day, although in secularised mutated forms. This Element deploys the intellectual history of medieval thought to map the moves made in codifying Mary's perfection. It then uses contemporary gender and affect theory to consider the implications of Mary's perfection within modernity, mapping the emotional regimes of the medieval past upon the present
Title from publisher's bibliographic system (viewed on 10 Jul 2020)
Keywords: Mary / Blessed Virgin, Saint / Theology; Mary / Blessed Virgin, Saint / History of doctrines